Determinant factors of women entrepreneurs' business performance: a conceptual framework - Md Isa @ Yusuff, Yusrinadini Zahirah; Abu Bakar, Azizi; Ahmad, Shuhymee (2016)
The inconsistent finding on the performance of women entrepreneurs is one of the gaps intended to be fill in by this paper.Previous studies found that men performance is greater than women and the majority of their business remains small and marginal.Literatures also indicate women owned business performed slightly better than men while others do not find gender based differentials in entrepreneurial performance.Indeed, controversy has arisen that women’s business have a higher rate of failure or lower performance compare to men’s business Thus, it is researcher’s concern to study the key factors contributing to the business performance of women entrepreneurs. In this regard, micro finance as financial capital and entrepreneurial competencies were the main variables with social capital and self-efficacy were taken into consideration in the proposed framework as the mediator and moderator. Theories from management and psychology also were discussed in this paper.